QUANTITATIVE AND QUALITATIVE COMPOSITION OF AXILLA MICROBIOTA IN PRACTICALLY HEALTHY INDIVIDUALS - O. Yu Borisova; A. V Aleshkin; N. T Gadua; S. S Bochkareva; B. A Efimov; V. A Chernova; V. A Aleshkin; L. I Kafarskaya; S. S Afanasiev; E. A Voropaeva; E. O Rubalsky; M. S Afanasiev; et al. (Журнал микробиологии, эпидемиологии и иммунобиологии, 2015)
Aim. Characteristics of quantitative and qualitative composition of cultured microorganisms isolated from axilla skin of practically healthy individuals. Materials and methods. 77 practically healthy individuals aged 18 to 40 years were examined. Species identification of microorganisms was carried out by culture-morphologic, tinctorial and biochemical properties using time-of-flight mass spectrometer and rpoB gene amplification with subsequent direct sequencing. Results. Quantitative evaluation of microbial composition of axilla skin microbiota in most of the practically healthy individuals varied in the 4 - 5 lg CFU/ml interval, whereas seeding of skin by this microbiota at the level of 8 lg CFU/ml was not detected. 158 strains of 24 microorganism species were identified in this biotope. Most of these strains (68.9%) belonged to Corynebacterium genus, 21.6% of strains - to Staphylococcus genus, 7.6% of strains - to Micrococcus genus and 1.9% of strains - Candida albicans. 16 species of corynebacteria were isolated with predomination of С. tuberculostearicum (40,3%), C. amycolatum (18,4%) and C. ureicelerivorans (14,8%) strains. The microbial landscape in most ofthe examined individuals (77.9%) was presented by microorganism association. Conclusion. Quantitative and qualitative species composition of cultured microorganisms isolated from axilla skin biotope of practically healthy individuals was characterized for the first time.